An MEK-cofilin signalling module controls migration of human T cells in 3D but not 2D environments - Klemke, Martin; Kramer, Elisabeth; Konstandin, Mathias; Wabnitz, Guido H.; Samstag, Yvonne (The EMBO journal, 2010)
T cells infiltrate peripheral tissues to execute immunosurveillance and effector functions. For this purpose, T cells first migrate on the two-dimensional (2D) surface of endothelial cells to undergo transendothelial migration. Then they change their mode of movement to undergo migration within the three-dimensional (3D)-extracellular matrix of the infiltrated tissue. As yet, no molecular mechanisms are known, which control migration exclusively in either 2D or 3D environments. Here, we describe a signalling module that controls T-cell chemotaxis specifically in 3D environments. In chemotaxing T cells, Ras activity is spatially restricted to the lamellipodium. There, Ras initiates activation of MEK, which in turn inhibits LIM-kinase 1 activity, thereby allowing dephosphorylation of the F-actin-remodelling protein cofilin. Interference with this MEK-cofilin module by either inhibition of MEK or by knockdown of cofilin reduces speed and directionality of chemotactic migration in 3D-extracellular matrices, but not on 2D substrates. This MEK-cofilin module may have an important function in the tissue positioning of T cells during an immune response.